Community Agroecological Values Framework: connecting the community capitals and agroecology to advance northern food system transformation in Kakisa, Northwest Territories, Canada - Temmer, Jennifer; Spring, Andrew; Simba, Ruby; Chicot, Lloyd (Frontiers in Climate, 2025)
Traditional food systems are central to cultural continuity, sustainable livelihoods, and food security for Indigenous communities in northern Canada. However, these systems are threatened by climate change, rising costs, and increasing reliance on purchased foods. At the same time, climate change presents opportunities to diversify through small-scale food production. Such initiatives can enhance food security and self-sufficiency but require tools that integrate Indigenous values and systems thinking. This research introduces the Community Agroecological Values Framework as a novel model for describing local food systems and guiding transformation in northern regions by prioritizing Indigenous values in community-led planning. In partnership with the Ka’a’gee Tu First Nation, this participatory action research uses qualitative methods to describe the current state of the community’s food system and outline a future vision and path to achieving community defined food system goals. Community members highlighted the need for increased access to local foods, greater youth engagement, and support to develop sustainable gardening skills. Insights informed the development of the Community Agroecological Values Framework, which builds on the Community Capitals Framework and Northern Agroecology to create a harmonized, systems-based and values-oriented planning framework and planning tool. This tool centers Traditional Knowledge and cultural values including land stewardship, reciprocal relationships, collective betterment, food sovereignty, self-determination, and intergenerational knowledge sharing, empowering communities to design and implement more resilient, culturally grounded, and self-sufficient food systems.